Genital lichen sclerosus/balanitis xerotica obliterans in men with penile carcinoma: a critical analysis. (29th January 2013) - Philippou, Prodromos; Shabbir, Majid; Ralph, David J.; Malone, Peter; Nigam, Raj; Freeman, Alex; Muneer, Asif; Minhas, Suks
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? The European Association of Urology guidelines identify lichen sclerosus (LS) as a strong risk factor for penile squamous cell carcinoma (pSCC). However, this statement is based on the findings of case–control studies (Level of Evidence 2a) and a direct causal relationship between LS/balanitis xerotica obliterans (BXO) and pSCC remains to be established. Firm guidelines with respect to the appropriate follow‐up policy for LS/BXO are lacking, whereas the impact of synchronous LS/BXO on the prognosis of pSCC remains to be determined. The presence of histologically‐confirmed synchronous LS/BXO in patients diagnosed with pSCC is relatively high, although it is not associated with an increased risk of adverse histopathological features. LS/BXO can develop in extragenital skin grafts used for reconstruction after organ‐sparing surgery for pSCC. Objectives To determine the rate of lichen sclerosus/balanitis xerotica obliterans (LS/BXO) in patients with penile squamous cell carcinoma (pSCC) and establish whether the presence of LS/BXO is associated with adverse histopathological features of pSCC. To report the phenomenon of LS involving non‐genital skin grafts in patients who underwent organ‐sparing surgery and split‐skin graft (SSG) reconstruction Patients and Methods Between January 2002 and January 2010, 223 men underwent surgical treatment for pSCC. A group of 52 patients with histologically‐confirmed synchronous LS was identified (group A; overall rate of LS/BXO = 23.3%) and compared with a group of patients without synchronous LS (group B; n = 171; 76.7%). A subgroup of patients who underwent surgical excision and SSG reconstruction was also identified The histology reports of graft biopsies obtained during follow‐up were reviewed and the rate of LS involving the graft was also recorded. Results Mean (range) age at diagnosis was 60.9 (34–81) years and 60.7 (28–89) years for groups A and B, respectively (P = 0.958). The mean (range) duration of follow‐up was 38.3 (4–92) months for group A and 45.5 (4–107) months for group B (P = 0.162) No statistically significant differences were noted between groups A and B in terms of tumour grade (P = 0.091), stage (P = 0.697), presence of lymphovascular invasion (P = 0.333), histological subtype (P = 0.107), associated carcinoma in situ (P = 0.246) or nodal status at initial diagnosis (P = 0.555). In the subgroup of 188 patients who underwent SSG reconstruction, 41 (21.8%) patients had histologically‐confirmed synchronous LS; in this subgroup, 26 (13.8%) patients underwent graft biopsy during follow‐up. Genital LS involving the graft was identified in seven specimens, although none of these seven cases had associated recurrent pSCC. Conclusions The presence of histologically‐confirmed synchronous LS in patients with pSCC is relatively high but is not associated with increased rates of adverse histopathological features, including carcinoma in situ. LS can develop in extragenital skin grafts, although its association with the long‐term risk for recurrent pSCC is not apparent in the present study.